The Impact of Taxation on Investment and Economic Growth: An Analysis of Tax Policies and Their Effects on Economic Performance - Zaneta, Ita Alexandria; Syalendra , Erika Sisi (Law and Economics, 2024)
This research investigates the impact of taxation on investment and economic growth, emphasizing the intricate relationships between various tax policies and economic behavior. Through a comprehensive analysis of corporate, personal income, and capital gains taxes, the study reveals that lower corporate tax rates significantly enhance investment levels, while high personal income taxes can deter consumer spending and consequently affect business investment. Additionally, the research introduces the Human Development Index (HDI) as a complementary measure to traditional economic indicators like GDP, underscoring the importance of considering social well-being in evaluating economic growth. Using a mixed-methods approach, including quantitative data analysis and qualitative insights from stakeholder interviews, this study provides a nuanced understanding of the effectiveness of tax incentives and the perceptions surrounding them. The findings highlight the need for competitive and equitable tax structures that incentivize investment and foster economic activity. Policy implications suggest that targeted tax incentives for innovation and sustainable practices can stimulate growth in key sectors, while transparency and fairness in tax policy are essential for building trust among taxpayers.